2022
DOI: 10.7554/elife.76436
|View full text |Cite
|
Sign up to set email alerts
|

trim-21 promotes proteasomal degradation of CED-1 for apoptotic cell clearance in C. elegans

Abstract: The phagocytic receptor CED-1 mediates apoptotic cell recognition by phagocytic cells, enabling cell corpse clearance in Caenorhabditis elegans. Whether appropriate levels of CED-1 are maintained for executing the engulfment function remains unknown. Here, we identified the C. elegans E3 ubiquitin ligase tripartite motif containing-21 (TRIM-21) as a component of the CED-1 pathway for apoptotic cell clearance. When the NPXY motif of CED-1 was bound to the adaptor protein CED-6 or the YXXL motif of CED-1 was pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Apoptosis performs a vital role as a T A B L E 1 List of different forms of protein palmitoylation. has been achieved (Yuan, Li, Jing, et al, 2022;Zheng et al, 2021).…”
Section: Mechanism Of Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis performs a vital role as a T A B L E 1 List of different forms of protein palmitoylation. has been achieved (Yuan, Li, Jing, et al, 2022;Zheng et al, 2021).…”
Section: Mechanism Of Apoptosismentioning
confidence: 99%
“…Moreover, apoptosis acts as a defensive mechanism during immunological responses or when cells are exposed to disease or harmful substances. Through the study of both lower model organisms and mammals, a certain understanding of the mechanisms of apoptosis has been achieved (Yuan, Li, Jing, et al, 2022; Zheng et al, 2021). Apoptosis is highly evolutionarily conserved and includes a strictly organized sequence of signaling cascade actions.…”
Section: Mechanism Of Apoptosismentioning
confidence: 99%
“…When the plasma membrane phagocytic receptor CED‐1 was activated, TRIM21 catalyzed K48‐linked poly‐ubiquitination on CED‐1 toward proteasomal degradation. [ 103 ] In converse, absence of TRIM21 accumulated CED‐1 post‐translationally and drove cell corpse degradation defects. [ 103 ] Immunoblot proved that suppressor of cytokine signaling 3 (SOCS3), a negative modulator of cytokines receptor required for normal cell development, bound to TRIM21 in thymic epithelial cells (TECs), and the Trim21 deficient mice show increased thymic production and the possibility was suggested that TRIM21 might target SOCS3 for degradation thus impairing the JAK kinase inhibition.…”
Section: Fc Independent Signalingmentioning
confidence: 99%
“…[ 103 ] In converse, absence of TRIM21 accumulated CED‐1 post‐translationally and drove cell corpse degradation defects. [ 103 ] Immunoblot proved that suppressor of cytokine signaling 3 (SOCS3), a negative modulator of cytokines receptor required for normal cell development, bound to TRIM21 in thymic epithelial cells (TECs), and the Trim21 deficient mice show increased thymic production and the possibility was suggested that TRIM21 might target SOCS3 for degradation thus impairing the JAK kinase inhibition. [ 70 ] Beyond stuffing in Figure 5, TRIM21 also directly binds to pathogens‐relative protein independent of interaction with Fc region of antibody to block further intracellular harm.…”
Section: Fc Independent Signalingmentioning
confidence: 99%
“…In C. elegans , two parallel redundant regulatory pathways control the process of engulfment of ACs. In the ced‐1/6/7 pathway [ 4 , 5 , 6 ], the phagocytic receptor CED‐1 recognizes ‘eat‐me’ signal phosphatidylserine (PS) [ 7 , 8 , 9 ]. In the ced‐2/5/12 pathway [ 10 , 11 , 12 , 13 ], several receptors including the phosphatidylserine receptor PSR‐1 [ 14 ], MOM‐5, and integrin INA‐1 [ 15 ] are proposed to recognize and bind to the PS.…”
mentioning
confidence: 99%